Evaluation of outcomes in a clinical trial: comparing self-fit hearing aids and hearing aids fit with best practices - Yellamsetty, Anusha; Lewis, Rebecca M. (Frontiers in Audiology and Otology, 2024)
The study aimed to determine whether a self-fitting algorithm for hearing aids could produce outcomes comparable to those achieved with professionally fitted hearing aids. Involving up to 40 subjects aged 18 to 80, the research compared two fittings: one conducted by a professionally trained audiologist Best Practice Fit (BP-FIT) and one using a self-fitting software (SELF-FIT). Subjects completed both fittings, with Real Ear Measures and Quick Speech In Noise (QuickSIN) measures taken before field use of either fitting. The subjects were randomly assigned to start with either SELF-FIT or BP-FIT, remaining unaware of their condition throughout the trial. After 2 weeks of hearing aid use in each condition, subjects provided subjective reports of perceived benefit (via the APHAB survey) and had their hearing aids reprogrammed for the remaining condition. The study assessed the efficacy through objective (REM), behavioral (QuickSIN), and subjective (APHAB) measures. In summary, the study findings reveal that the SELF-FIT hearing aid system performed similar to the BP-FIT across multiple domains. This includes objective measures of self-fitting hearing aid output assessed through REM, with a difference of <5 dB SPL between fitting conditions, behavioral evaluation of speech understanding in background noise via QuickSIN, with a difference of <2.7 dB SNR between fitting conditions, and subjective assessment of efficacy as reported by the user via APHAB, with a difference of <10% between fitting conditions.